(3aj GdGbJUGO GdGSdGej h GdGbJUGO GdhVYjs - (3SdjeGf YeQ eMeO(B, (3GdgGOjs ((3YeGf(B:s (3GdGcGOejhf ddfTQ(B,s, 2010)
(3eaGgje h CacGQ aj GdHjFI h GdGSJKeGQ h bVGjGgeG GdGSGSjI eY GdJWQb Edi eaghe GdHjFI h GdGSJKeGQ GdGLfHj GdeHGTQ h eaghe GdMbhb , GdGSJKeGQ GdGLfHj GdeHGTQ h BKGQg aj GdHjFI GdGbJUGOjI HGdJWQb Edi GdehGQO GdWHjYjI , QCS GdeGd h GdYeGdI , GdGfJGL , GdGSJgdGc h GdHjFI , GdGSJKeGQ GdGLfHj GdeHGTQ h BKGQg aj GdHjFI GdGLJeGYjI HGdJWQb Edi GdMVGQI h GdHjFI , , JCKjQ GdGSJKeGQ GdGLfHj aj GdeaGgje h GdHjFI GdGLJeGYjI , JgejT GdYbjOI , GdGSJKeGQ GdGLfHj GdeHGTQ hBKGQg aj GdHjFI GdSjGSjI HGdJWQb Gdi GdOhdI , BdjGJ GdOjehbQGWjI h eHOCGdThQi h bhI GdOhdI , YhdeI GdGYdGe h GdKbGaI (B.s
(3eQGLY U(B.203s
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdESdGejs; (3GdGSJKeGQ GdCLfHjs; (3GdHjFIs